2020
DOI: 10.1038/s41598-020-78490-0
|View full text |Cite
|
Sign up to set email alerts
|

The mineralogy and structure of use-wear polish on chert

Abstract: Polished edges of archaeological stone tools are commonly investigated to obtain information on the tools’ uses in prehistory. Yet to this day, it remains unclear what exactly such polishes are and how they form. Answering these questions should allow the elaboration of new interpretative methods based on objective measurements. Two major competing hypotheses of polish formation have been proposed: abrasion and the formation of a thin amorphous film on the chert or flint surface. We employ reflectance infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…are softer than stone and cannot, in theory, abrade the stone tools themselves. However, given that stone tools are, in fact, abraded by contact with softer materials [23][24][25], why does this happen, and which factors related to the target material play the most significant role? Our counterintuitive result suggests that the abrasion 'paradox' must be explained by either the presence of hard grits within the worked material, the presence at the interface of stone particles broken off the tool edge, or a combination of both [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…are softer than stone and cannot, in theory, abrade the stone tools themselves. However, given that stone tools are, in fact, abraded by contact with softer materials [23][24][25], why does this happen, and which factors related to the target material play the most significant role? Our counterintuitive result suggests that the abrasion 'paradox' must be explained by either the presence of hard grits within the worked material, the presence at the interface of stone particles broken off the tool edge, or a combination of both [53].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in another paper related to this experimental setup [25], polish is formed by abrasion of the flint surface. Consequently, we expect that harder worked material would be more effective in creating polish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different theories have been postulated as to the nature of these alterations (adsorption theory vs dissolution theory), incidentally, however, as Rottländer (1975) pointed out, the difficulties in experimentally replicating these alterations and the lack of a unified terminology of 'patination', hamper understanding the origins of these alterations. Recently, Schmidt et al (2020) demonstrated using reflectance infrared microscopy that usewear polish on chert has its origins in a physical process (abrasion), making it possible to infer a similar origin for the formation of taphonomic surface modifications; nonetheless, additional research into the subject remains to be undertaken.…”
Section: Taphonomic Alterations Of Archaeological Remainsmentioning
confidence: 99%